2007
DOI: 10.1002/ep.10234
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst development for stable hydrogen generation during steam reforming of renewable and nonrenewable resources

Abstract: The production of hydrogen from renewable and nonrenewable resources is demonstrated. Catalytic steam reforming, using a rhodium-containing catalyst, is shown to be effective for the conversion of natural gas and n-hexadecane (used as a simulant for diesel fuel). Improved conversion efficiencies can be achieved by performing the reaction at higher temperatures and steam to carbon ratios. The presence of sulfur in the fuel is shown to have a significant inhibiting effect on catalyst performance. Steam reforming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 13 publications
(10 reference statements)
0
13
0
Order By: Relevance
“…In fact, Resende and Savage showed a huge jump on hydrogen and methane yield when temperature increased from 500 to 600 C in the gasification of cellulose, indicating that gas yield follows an arrhenius variation with temperature and that temperature is dominant variable for increasing gas yield [45]. It is noteworthy that the reactor system could yield almost the theoretical maximum of hydrogen (12 mol/mol glucose) at temperatures above 740 C. Its performance was comparable to atmospheric steam reforming at 700e800 C with catalysts such as 15e30 wt% Ni/Al 2 O 3 [48,49], PdeNieCu-K/Al 2 O 3 [50], and 10 wt% NiO/YSZ (yttria-stabilized zirconia) [51].…”
Section: Effects Of Reaction Temperaturementioning
confidence: 90%
“…In fact, Resende and Savage showed a huge jump on hydrogen and methane yield when temperature increased from 500 to 600 C in the gasification of cellulose, indicating that gas yield follows an arrhenius variation with temperature and that temperature is dominant variable for increasing gas yield [45]. It is noteworthy that the reactor system could yield almost the theoretical maximum of hydrogen (12 mol/mol glucose) at temperatures above 740 C. Its performance was comparable to atmospheric steam reforming at 700e800 C with catalysts such as 15e30 wt% Ni/Al 2 O 3 [48,49], PdeNieCu-K/Al 2 O 3 [50], and 10 wt% NiO/YSZ (yttria-stabilized zirconia) [51].…”
Section: Effects Of Reaction Temperaturementioning
confidence: 90%
“…Glycerol reforming over a c-Al 2 O 3 -supported Pd/Ni/Cu/K catalyst was studied in [24] and [34] in the temperature range of 500 to 800°C. It was found that the steam reforming process was limited by char formation.…”
Section: Nickel Catalystsmentioning
confidence: 99%
“…By contrast, other metals require some promoters to ensure similar performances. [40,49,51] A wide range of supports for the active metal sites in the glycerol SR reaction has also been tested, varying from acidic [35] to basic, [47] in many cases without paying attention to the non-innocent role of these materials in the catalytic process. An efficient catalyst for H 2 production from glycerol is expected to break-up the substrate through CÀC, OÀH, and CÀH bond cleavages, at the same time promoting the elimination of metal-passivating carbon monoxide via the WGS reaction.…”
Section: Introductionmentioning
confidence: 99%